2007
DOI: 10.11606/issn.2316-9079.v6i2p83-103
|View full text |Cite
|
Sign up to set email alerts
|

Physiology, environmental change, and anuran conservation

Abstract: Physiology, environmental change, and anuran conservation. This paper reviews diverse ways in which the emerging discipline of conservation physiology may contribute to the conservation of anuran amphibians. We first present a summary of the goals of conservation physiology. Then, we review five specific sources of environmental change that are known to affect anurans: introduced pathogens (highlighting the case of chytridiomycosis) and exotic species, pollutants, habitat fragmentation, and global climate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 180 publications
2
38
0
7
Order By: Relevance
“…Ectothermic species are particularly sensitive to environmental change (Navas and Otani 2007). The current, modeled distribution of Melanophryniscus montevidensis based on climate conditions, coincides with previous distributions proposed for this species (BernardoSilva et al 2012, IUCN 2013.…”
Section: Discussionsupporting
confidence: 87%
“…Ectothermic species are particularly sensitive to environmental change (Navas and Otani 2007). The current, modeled distribution of Melanophryniscus montevidensis based on climate conditions, coincides with previous distributions proposed for this species (BernardoSilva et al 2012, IUCN 2013.…”
Section: Discussionsupporting
confidence: 87%
“…The presence of at least four species endemic to the state of Rio de Janeiro attest to the importance of the PETP as a conservation unit for anuran species, which are currently facing a worldwide decline due to factors such as global climate change, pollution, habitat loss, and the spread of diseases such as chytridiomycosis (e.g. YOUNG et al 2004, TOLEDO et al 2006, NAVAS & OTANI 2007.…”
Section: Discussionmentioning
confidence: 99%
“…In the only study coincident with the areas of endemism found for terrestrial vertebrates. Anurans are sensitive to environmental degradation and considered to be among the most vulnerable vertebrate groups (Navas and Otani 2007). In Brazil, 41 anuran species (ca.…”
Section: Introductionmentioning
confidence: 99%